The synergism of lytic polysaccharide monooxygenases with lichenase and their co-immobilization on silica nanospheres for green conversion of lichen biomass - Cai, Lixi; Zheng, Ying; Chu, Yunmeng; Lin, Yuanqing; Liu, Lixing; Zhang, Guangya (Frontiers in Nutrition, 2022)
Enzyme-assisted valorization of lichenan represents a green and sustainable alternative to the conventional chemical industry. The recently discovered lytic polysaccharide monooxygenases (LPMOs) are essential components of state-of-the-art enzyme cocktails for lichenin bioconversion. The LPMOs named AST from Chaetomium globosum was functionally expressed in E. coli and exhibited 1.25-fold synergism with lichenase, whereas AST alone produced no detectable reducing sugars. The HPLC results further confirm that AST does not alter the endogenous hydrolysis mode of lichenase but rather enhances its hydrolysis efficiency by disrupting the long chain of lichenan and releasing more reducing ends. To the best of our knowledge, this was the first report on the synergistic effect of LPMOs and lichenase, which may have great synergistic potential in the conversion of lichen biomass. Furthermore, a novel strategy for the covalently immobilizing AST and lichenase on silica nanoparticles from the cell lysate in a single step was proposed, which exhibited high activity recovery (82.9%) and high immobilization yield (94.8%). After 12 independent runs, about 68 % of the initial activity of the immobilized enzymes was retained. The resulted biocatalyst systems exhibited the green and sustainable strategy in the bioconversion of lichen biomass as well as other diverse polysaccharides.